IMF Research Bulletin, December 2009. (IMF Research Bulletin; IMF Research Bulletin ;, 2010)
This paper examines credit conditions and recoveries from financial crises. The paper highlights that the prospects for recovery from the 2008 global financial crisis appear to be on the horizon. The paper discusses that the question-what determines the path of recovery from a recession associated with a financial crisis-is of utmost importance as policymakers debate how soon to withdraw the extraordinary monetary and fiscal stimulus that were put in place soon after the onset of the crisis. The paper also analyzes inflation targeting in emerging economies.